Isolation of a Diylide‐Stabilized Stannylene and Germylene: Enhanced Donor Strength through Coplanar Lone Pair Alignment. Issue 22 (17th April 2019) - Mohapatra, Chandrajeet; Scharf, Lennart T.; Scherpf, Thorsten; Mallick, Bert; Feichtner, Kai‐Stephan; Schwarz, Christopher; Gessner, Viktoria H.
Abstract: The preparation of the first stable diylide‐substituted stannylene and germylene (Y2 E, with E=Ge, Sn and Y=[PPh3 ‐C‐SO2 Tol] − ) is reported. The synthesis is easily accomplished in one step from the sulfonyl‐substituted metalated ylide YNa and the corresponding ECl2 precursors. Y2 Ge and Y2 Sn exhibit unusual structures in the solid state and in solution, in which the three adjacent lone pairs in the C‐E‐C linkage are arranged coplanar to each other. As shown by DFT studies, this bonding situation is preferred over the typical π‐donation from the ligands into the empty p‐orbital at the metal due to the strong anion‐stabilizing ability of the sulfonyl groups in the ylide backbone and their additional coordination to the metal. The alignment of the three lone pairs leads to a remarkable boost of the HOMO energy and thus of the donor strengths of the tetrylenes. Hence, Y2 Ge and Y2 Sn become stronger donors than their diamino or diaryl congeners and comparable to cyclic alkyl(amino)carbenes. First reactivity studies confirm the high reactivity of Y2 Ge and Y2 Sn, which for example undergo an intramolecular C−H activation reaction via metal–ligand cooperation. Abstract : Boost me up ! The first diylide‐substituted germylene and stannylene compounds Y2 Ge and Y2 Sn were prepared by salt metathesis using a metalated ylide. The tetrylenes exhibit unusual structures in which the three lone pairs at the adjacent C‐E‐C atoms are coplanarly arranged. This bonding situation results in a remarkable increase of the HOMO energy and the donor strength, thus making these tetrylenes donors as strong as cyclic alkyl(amino)carbenes.